Relationship between lipid profile, cardiac hemodynamics status and autoimmune activation markers in patients with ischemic heart disease, accompanied with hypothyroidism - N. S. Mykhailovska; T. V. Oliynyk (Zaporožskij Medicinskij Žurnal)
Presence of hypothyroidism in patients with coronary heart disease contribute to its progression. Aim. Study purpose was exploring the features of changes in lipid profile, cardiac hemodynamics status, autoimmune activation markers and their relationships in patients with coronary heart disease, accompanied with hypothyroidism. Methods and results. 64 patients were examined. The levels of thyroid-pituitary hormones, concentration of tumor necrosis factor-α, C-reactive protein, endothelin-1, an inhibitor of plasminogen activator-1, neopterin were examined by ELISA. Structural and functional heart features were studied with doppler echocardiography. It was found that patients with coronary heart disease, accompanied with hypothyroidism, had more expressed lipid disorders, heart restructuring such as increased end - diastolic volume, end - diastolic pressure, myocardial mass and stiffness index on the background of immunoinflammatory activation and endothelial dysfunction. Conclusions. It was found correlation between markers of endothelial dysfunction immunoinflammatory activation and lipid profile, heart structural and functional state.